EFFECT OF PLASTIC DEFORMATION AND WELDING ON CORROSION BEHAVIOUR OF 304 MATERIAL IN SIMULATED FLUE GAS DESULFURIZATION - Nur Lathifa, Aulia
Corrosion behavior of stainless steel 304 and its weldment welded under bending load in simulated flue gas desulfurization (50wt.% H2SO4, 2wt.% HCl, 1.5wt.% HNO3, and 0.2wt.% HF) at 60 °C investigated by combining immersion testing and surface analyses. Weld metal morphology and microstructural characteristics of welds were investigated. Dendritic structures are found in the weld metal. Corrosion evaluation was conducted by weight loss measurements and metallographic observations to determine the type of corrosion attack. After the corrosion test, the sample showed selective austenite/ferrite interface corrosion in base metal and weld metal. The test results indicated pitting corrosion was the dominant type of corrosion attack in the weld metal. Weight loss of the 304 materials in the simulation of the Flue Gas Desulfurization (FGD) environment is getting higher. Plastic deformation will cause an increase in weight loss because a potential difference is formed due to strain in the material. Variations in microstructure due to welding can cause an increase in weight loss due to the formation of a Cr depletion zone around the delta ferrite.